An overview of menopause, and why this should feature within pre-registration education - Calow, Alice; Morrell-Scott, Nicola; Smith, Emma Johnson (British journal of nursing (Mark Allen Publishing), 2023)
Over half the population (51%) of England and Wales is female, most of whom will experience menopause, either as a result of endocrine ageing or medical treatment. The project aimed to undertake a review of the literature to determine the level of knowledge about menopause that healthcare students are exposed to, and to highlight why it is important for them to have an understanding of this subject both for their own clinical practice and for supporting colleagues in the workplace. A literature review was conducted by the project team. There is a lack of education for healthcare students, who will go on to care for those affected by menopause, and will also work with colleagues experiencing menopause. Educational programmes should include menopause as a component, which will allow for a breaking down of barriers on a subject that is still generally considered taboo. A national audit should be conducted on menopause coverage in UK pre-registration nursing. The addition of menopause to the Liverpool John Moores University pre-registration nursing curriculum is also recommended based on agreed competencies.